Status of common sexually transmitted infection in population referred for colposcopy and correlation with human papillomavirus infection - Disi A; Jiayue Li; Dai Zhang; Bingbing Xiao; Hui Bi (BMC, 2023)
Abstract Background To investigate the prevalence of common sexually transmitted infections (STIs) and the association of STI/human papillomavirus co-infection in young and middle-aged women with previous abnormal cervical findings referred for colposcopy. Methods 719 cervical-swab cytobrush specimens were obtained from women aged ≤ 50 years who were referred for colposcopy at Peking University First Hospital due to previous abnormal cervical findings. HPV 21 typing and a panel of pathogenic STIs were tested for using the 21 HPV GenoArray Diagnostic Kit (HBGA-21PKG; HybriBio, Ltd., Chaozhou, China) and a nucleic acid STI detection kit (HybriBio Ltd. Guangzhou, China), after which colposcopy with multipoint positioning biopsy was performed. Results The overall prevalence of STIs among HPV positive women with previous abnormal cervical cancer screening results was 63.7% (458/719), with Ureaplasma parvum serovar 3, Ureaplasma parvum serovar 6 and herpes simplex virus type 2 having significantly higher prevalence among high-risk HPV positive patients (19.3%, Χ2 = 5.725, P = 0.018; 21.5%, Χ2 = 4.439, P = 0.035; 5.7%, Χ2 = 4.184, P = 0.048). Among patients positive for the high-risk human papillomavirus, the prevalence of Neisseria gonorrhoeae infection in human papillomavirus 16/18 positive patients was significantly higher than that in other patients (2.5%, Χ2 = 4.675; P = 0.043). Histopathologically, Chlamydia trachomatis infection was more frequently detected in lower than or equal to low-grade squamous intraepithelial lesion infection status (13.0%, Χ2 = 3.368; P = 0.041). Conclusions The high prevalence of HPV coinfection with other sexually transmitted pathogens, particularly Ureaplasma parvum serovar 3, Ureaplasma parvum serovar 6, and herpes simplex virus type 2, calls for routine STI screening and effective STI prevention and management in patients with abnormal cervical cancer screening results.